The Influence of Maternal Social Deprivation on Undernutrition in Children Under 5 Years in Northern and Southern Nigeria - Obi, Nkiru Jacinta; Harris, Jenine (Journal of Maternal and Child Health, 2023)
Background: Undernutrition is a global public health issue that has far-reaching consequences on the health and development of individuals as well as economic and social impacts on communities and countries. Middle and low-income countries like Nigeria bear the highest burdens and Nigeria has an unequal distribution of this burden between the North and South. Maternal socioeconomic factors have been implicated in the burden of undernutrition. This study examines the regional differences in these factors as key determinants of the inequalities in the distribution of the burden of undernutrition. Subjects and Method: We conducted a secondary data analysis of the child-recode data set from the cross-sectional 2018 Nigerian Demographic Health Survey (NDHS). NDHS participants were selected from all thirty-six states in Nigeria and the Federal Capital Territory (FCT) via a two-stage stratified cluster design. The child-recode data set includes 33,924 children aged 0 to 59 months. The dependent variables are weight for age, height for age, and weight for height. Independent variables of interest include the mother’s education, mother’s employment status, wealth quintile, and residence. Additional confounders included the age and sex of the child. Bivariate and multivariable logistic regression models were used to examine the association between region, maternal deprivation factors, and undernutrition. Results: The unadjusted odds of being underweight (OR=2.80; 95% CI=2.53 to 3.10; p<0.001), stunted (OR=3.09; 95% CI=2.84 to 3.37; p<0.001), or wasted (OR=1·91; 95% CI=1.62 to 2.28; p<0.001) were statistically significantly higher in children living in the North compared to children in the South. Across all 3 indices of undernutrition, the most consistent factors affecting childhood undernutrition were the mother's education (no formal education) and wealth quintile (poorest households). The regional differences in the prevalence of undernutrition persisted, after accounting for maternal deprivation factors that are more prevalent in the Northern parts of Nigeria. Conclusion: Policies and programs to improve childhood undernutrition should be community-centered and focus on mitigating the inequities in important contributory factors. Further research to explore the role of childhood infections and environmental factors such as water, sanitation, and hygiene in the regional differences in undernutrition in Nigeria is needed. Keywords: nutrition, social deprivation, Nigeria, children. Correspondence: Nkiru Jacinta Obi. Washington University in St. Louis, 1 Brookings Drive, St. Louis, Missouri. Mobile: 513-3027517. Email: nkiruobih@gmail.com.